EFFICIENCY OF QUALITY MANAGEMENT SYSTEMS OF RETAIL ENTERPRISES - Самойленко, Антоніна; Кулік, Анна; Захарченко, Петро (Modern engineering and innovative technologies, 2023)
Methodological approaches to the analysis of the construction goods quality management system are considered in the article. The groups of rating parameters of the construction goods quality management system of the investigated enterprise (Epicenter K LL